DINASTI GOLDEN HORDÉ PEMBACAAN HISTORIS TERHADAP KEKUASAAN MONGOL ISLAM DI ASIA TENGAH - M. Abdul Karim (Jurnal Kawistara, 2016)
It is very interesting to study and examine the history of Mongolian nation. First, they were nomadicand uncivilized nation, but after Mongol had developed, they became an important general in theworld. One of the Golden Age of Mongolian Nation, after they had accepted Islam. Islamic spirit becameprominent characteristic during the period of the government of Golden Hordé Dynasty, which alsopopular with Kipcak Dynasty. This dynasty developed and became a new political authority, whichwas respected by the other dynasties. Based on the Islamic doctrine, they developed their governmentpolicy. Although Golden Hordé kept on their tradition, Islam still became dominant. This study focuson the process of regeneration and the change of political authority in the realm of Mongol. By usingcomprehensive literature approach, this study takes an important theme, which is rarely expressed byother studies. The contribution (originality) of this study is very important for Muslim community nowand in the future.